2020
DOI: 10.1107/s2052252519015471
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing contributions of ceramic matrix and binder metal to the plasticity of nanocrystalline cermets

Abstract: Using the typical WC–Co cemented carbide as an example, the interactions of dislocations within the ceramic matrix and the binder metal, as well as the possible cooperation and competition between the matrix and binder during deformation of the nanocrystalline cermets, were studied by molecular dynamics simulations. It was found that at the same level of strain, the dislocations in Co have more complex configurations in the cermet with higher Co content. With loading, the ratio between mobile and sessile dislo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, when exposed to high-velocity impacts, FCMCs often fail due to severe fractures, resulting in substantial structural impairments. Consequently, an in-depth understanding of FCMCs' fracture behavior under high-strain rate conditions is critical for improving their impact resistance through structural and compositional enhancements [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when exposed to high-velocity impacts, FCMCs often fail due to severe fractures, resulting in substantial structural impairments. Consequently, an in-depth understanding of FCMCs' fracture behavior under high-strain rate conditions is critical for improving their impact resistance through structural and compositional enhancements [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized, as well, that cemented tungsten carbide, which is usually used in coatings, has some degree of plasticity, especially when compressive loads are applied [4]. Moreover, it is shown that at the later deformation stage dislocations' density of WC in cermet dominates, indicating a more important WC role in the plasticity than a role of a metal binder [5]. This gives an advantage to WC over brittle hard materials.…”
Section: Introductionmentioning
confidence: 99%